Characteristics of formation of spring rape productivity under the influence of seeding rate and fertilizing - Гарбар, Л. А.; Антал, Т. В.; Романов, С. М. (Scientific Progress & Innovations, 2016)
The article provides the results of the research aimed to study the effect of the use of fertilizers and seeding rates on formation of productivity of crops of different varieties of spring rape. Research was conducted during 2013–2015 in terms of Cherkasy region in typical black soil. As a result of the studies it was found that in the typical low-humic black soil in Forest-Steppe zone of Ukraine the highest increase in yield of spring rape seed varieties Magnat and Sirius is formed by fertilization in norm of N70P40K70 and seeding rate of 1,2 million of sprout seeds per 1 ha.